Komodifikasi Tradisi Bedah Blumbang sebagai Objek Wisata Budaya di Kabupaten Semarang - Af’idatul Lathifah; Reny Wiyatasari (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
Tourism is one of the most important sectors in the development process in the country of Indonesia. Cultural tourism development in various regions has led to cultural commercialization practices. Cultural commercialization includes the reconstruction of art and traditions and the practice of everyday life into stage performances that can be enjoyed by tourists. Gintungan Hamlet is one of the hamlets located at the of Mount Ungaran. In this hamlet there is a spring (pennant). The spring has until now become the center of the bedah blumbang ritual. Bedah blumbang that has been going on for decades has inevitably experienced various changes. These changes include changes in the procedures for implementing, completing ceremonies, and involving the community. At the stage of the procession, the tradition of blumbang surgery has become a place for cash exchange market activities with bazaar performances. The commodification of tourism in this blunt surgical tradition has a negative and positive impact. The negative impact is that there are various fundamental changes in its implementation, especially in determining the timing of implementation. The positive impact is that tourism development is also accompanied by infrastructure development that can be used widely by the people of Gintungan Hamlet, the opening of information from inside and outside the hamlet, and revitalizing the tradition of blunt surgery. this research uses ethnographic methods